Penerapan Metode Simple Additive Weighting (SAW) Dalam Mengelompokkan Kualitas Kacang Kedelai Di Rumah Tempe A-Zaki Padang - Nissa, Ika Ima; Yuhandri, Y; Nurcahyo, Gunadi Widi (STIKOM Tunas Bangsa Pematangsiantar, 2024)
Soybeans are a legume that has quite high protein levels. This Decision Support System uses the Simple Additive Weighting (SAW) method. This method has seven stages, namely determining the criteria and criteria weight values, determining the suitability rating of each alternative for each criterion, determining the normalization value and weight attribute, determining the decision matrix, determining the normalized matrix value, calculating the matrix by adding up the respective criteria matrices, alternatively do Ranking. The data processed in this research comes from Rumah Tempe A-Zaki Padang. The data consists of 4 alternatives, namely green soybeans, yellow soybeans, black soybeans, brown soybeans with 5 assessment criteria, namely color, texture, cost, aroma, taste which are used to apply the Simple Additive Weighting (SAW) method. The results of this research are that green soybeans have the highest value with a yield of 0.8525, yellow soybeans with a yield of 0.755, brown soybeans with a yield of 0.6345 and the lowest value with a yield of 0.6275. Therefore, the Decision Support System designed can help increase accuracy in determining the quality of soybeans using the Simple Additive Weighting (SAW) method and provide information for Rumah Tempe A-Zaki Padang in making decisions regarding the best quality of soybeans.